O39-1 Calculating the future excess fraction of occupational cancer in australia. (1st September 2016) - Carey, Renee; Driscoll, Timothy R; Glass, Deborah C; Rushton, Lesley; Darcey, Ellie; Reid, Alison; Si, Si; Hutchings, Sally J; Peters, Susan; Fritschi, Lin
Abstract : Background: In 2012, approximately 3.6 million Australian workers (40% of the Australian workforce) were estimated to be exposed to occupational carcinogens in their current job. Estimating the burden of cancer resulting from these occupational exposures is a useful tool for policy planning around preventing or reducing exposure in the workplace. This study aims to estimate the future excess fraction of cancer resulting from current occupational exposures among Australian workers. Methods: The future excess fraction method estimates the proportion of exposure-related cancers occurring over a number of years in the future in those people who were exposed in a specific year. We used this method to estimate the future lifetime risk of occupational cancer (2012–2094) among Australian workers estimated to have been exposed to any of 38 carcinogens at work in 2012. Calculations were conducted for 19 different cancer types and a total of 53 cancer-exposure pairings. Results: Our cohort of 14.5 million Australians who were of working age in 2012 will develop an estimated 4.8 million cancers during their lifetime, of which 1.4% (approximately 68, 500 cancers) are attributable to occupational exposure for those exposed in 2012. The cancer sites with the highest number of predicted exposure-related cases are lung (n = 26, 000), leukaemia (n = 8, 000), and mesothelioma (n = 7, 500). The carcinogens which are estimated to contribute most are asbestos (n = 13, 500), solar ultraviolet radiation (n = 10, 000), and benzene (n = 8, 000). Conclusions: A significant proportion of future cancers in the Australian population will result from occupational exposures. The estimate presented here is lower than previous estimates in the literature; however, our estimate is not directly comparable to previous estimates as a result of different methodologies. The results of this study allow us to determine which current occupational exposures are most important, and where exposure prevention might best be targeted.